2006
DOI: 10.1158/0008-5472.can-05-3529
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Breast Cancer Cells by CD8+ Cytotoxic T-Cell Clones Specific for NY-BR-1

Abstract: Immunotherapy for breast cancer using cytotoxic T cells (CTL) is hindered by the lack of well-characterized breast cancer antigens that are expressed in most breast tumor cells and recognized by CD8 + CTL. A recently described breast tissue differentiation antigen, NY-BR-1, is expressed in >80% breast tumors and elicits a humoral response in a subset of breast cancer patients. To identify potential NY-BR-1 epitopes that are recognized by CTL, CD8 + T cells were stimulated in vitro with autologous dendritic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 33 publications
0
36
0
1
Order By: Relevance
“…In view of its highly restricted expression pattern, ANKRD30A may be considered as a breast M Lacroix: Disseminated breast cancer cells www.endocrinology-journals.org differentiation antigen that could represent a suitable target for immunotherapy , Wang et al 2006. Indeed, it was found in 80% of breast cancer specimens, while tumours of other histological types were ANKRD30A-negative.…”
Section: Ankrd30amentioning
confidence: 99%
“…In view of its highly restricted expression pattern, ANKRD30A may be considered as a breast M Lacroix: Disseminated breast cancer cells www.endocrinology-journals.org differentiation antigen that could represent a suitable target for immunotherapy , Wang et al 2006. Indeed, it was found in 80% of breast cancer specimens, while tumours of other histological types were ANKRD30A-negative.…”
Section: Ankrd30amentioning
confidence: 99%
“…Genetic mutations resulting in the aberrant expression or overexpression of determinants commonly expressed by nonmalignant cells seem to underlie their immunogenic properties. MUC1 (19,20), HER2/neu (21), p53 (22,23), and NY-BR-1 (24)(25)(26) are aberrantly expressed by the malignant cells of breast cancer patients. It is likely that these are only a few representations of an array of tumor antigens that characterize the malignant cell population.…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al (Hui et al 2009) analyzed that hepatocellular carcinoma patients received post-operative CIK cells therapy that may prevent recurrence and metastasis. Other preclinical and clinical trials also demonstrated that application of CIK cells had approved beneficial for patients with malignant tumors, such as gastric cancer (Sun et al 2005), renal cell carcinoma (Wang et al 2006) and so on. In our study, 25 patients of all patients were alive, median follow-up was 34.9 months (range, 4-69), and the percentages of CD3 ?…”
Section: Discussionmentioning
confidence: 97%